Gender Relations in The Technical Education Field - Solihati, Nessy; Ana, Ana (INVOTEC, 2019)
Harmonious gender relations between men and women is needed to achieve gender equality and gender equity. The purpose of this article is to find out gender relations in engineering, especially mechanical engineering in metal casting. Relationships between male and female students and relations between male and female students and lecturers. The qualitative research is the Phenomenology technique. The informants in this study were 10 students with 4 men and 6 women and a lecturer in a Polytechnic Bandung. The results showed that the relation between male and female students did not make any difference in the process of theory and practice learning. The relationship between lecturers, male, and female students also established without any difference in the men and women gender in carrying out the task of theory and practice learning. A patriarchal culture that hinders interaction between men and women genders and lecturers who used to be attached to the engineering field has begun to disappear. The research development on gender relations in engineering must still be the focus of scientists research.